Joint Moments During Downhill and Uphill Walking of a Person with Transfemoral Amputation with a Hydraulic Articulating and a Rigid Prosthetic Ankle—A Case Study. Issue 1 (January 2018) - Alexander, Nathalie; Strutzenberger, Gerda; Kroell, Josef; Barnett, Cleveland T.; Schwameder, Hermann
ABSTRACT: Introduction: Functional characteristics of prosthetic ankle design may facilitate sloped walking for individuals with transfemoral (TF) amputation. The aim of the current case study was to analyze the effects of a rigid versus a hydraulically articulating ankle component on the biological joint moments of an individual with TF amputation during downhill, uphill, and level walking. Materials and Methods: The gait of one individual with unilateral TF amputation, using the same prosthetic foot with rigid and hydraulic ankle components, was analyzed and compared with a control group of 18 able-bodied participants. Kinematic and kinetic data were recorded at self-selected walking speed on a sloped ramp with inclinations of −12°, −4° (downhill), 0° (level), +4°, and +12° (uphill). Results: The slope influenced lower-limb joint moments similarly in both the able-bodied participants and the participant with unilateral TF amputation. The effect of altering ankle movement through exchanging prosthetic ankle componentry was most acutely seen at the hip joint of the residual limb. The use of a hydraulic ankle joint component resulted in decreased mean hip joint extension and flexion moments of up to 92% and 48%, respectively, in the residual limb when compared with the use of the rigid ankle joint component. Conclusions: During sloped walking, the use of a hydraulically articulating versus rigid ankle joint component reduced the joint moments observed at the hip joint of the residual limb in an individual with unilateral TF amputation. This indicates a benefit for persons with TF amputation as the increased ankle function reduces the moment producing requirements of the hip joint, which may result in decreased energy consumption and subsequently a more efficient gait.